Being at home: Global citizenship in Norwegian schools. A study of children’s poems - Erdmann, Susan; Gawronska, Barbara (LingBaW. Linguistics Beyond and Within, 2016)
The paper addresses the question of self-perceived identity in children attending international schools in Norway. In this population, the distinction between “home culture” and “host culture” is no longer relevant, since most of the children represent “hyphenated” (e.g. Asian-British or American-Scandinavian) or merged nationalities and cultures. The goal of the study is to investigate how these pupils define themselves and the notion of “home”. To achieve at least a preliminary picture of the children’s self-perception, the authors have analysed poems on two topics: Me and Home, written by pupils of an international school and a Norwegian school, both informant groups aged 11-13. A semantic analysis of the poems indicates that the international school children present strong assertions of individual identity as defined against societal roles, while the Norwegian school pupils do not conceptualize identity formation as a struggle and their poems reflect a high degree of social, familial and national integration.